Using cerebral regional oxygen saturation and amplitude-integrated electroencephalography in neonates on extracorporeal membrane oxygenation: preliminary experience from a single center - Ling-Shan Yu; Xiu-Hua Chen; Si-Jia Zhou; Yi-Rong Zheng; Zeng-Chun Wang; Qiang Chen (BMC, 2024)
Abstract Objective This study aims to evaluate the application value in neurological outcome of cerebral regional oxygen saturation (CrSO2) and amplitude-integrated electroencephalography (aEEG) monitoring during neonatal extracorporeal membrane oxygenation (ECMO) courses. Methods We retrospectively analyzed 18 neonates receiving veno-arterial ECMO (V-A ECMO) support at our hospital from July 2021 to December 2022. Continuous monitoring of CrSO2 and brain electrical activity was conducted using near-infrared spectroscopy (NIRS) and aEEG throughout the ECMO treatment. We collected and analyzed related clinical data. Results Among the 11 survivors, 5 were categorized as the normal group (N group) and 6 as the abnormal group (AN group) based on post-ECMO brain MRI outcomes. The N group exhibited shorter time percentage of significant CrSO2 reduction (> 25% from baseline or absolute value < 40%), better fractional tissue oxygen extraction (FTOE) rates, and more stable mean percentage changes in CrSO2 compared to the AN group. Neonates in the N group predominantly showed mildly abnormal aEEG readings, with one patient displaying disrupted sleep-wake cycles. This particular patient also had more significant CrSO2 reduction and poorer FTOE compared to others in the N group. Additionally, the Test of Infant Motor Performance (TIMP) scores indicated hypoevolutism in this patient before discharge, while others in the N group had normal TIMP scores. In the AN group, 4 exhibited moderate and 2 severe aEEG abnormalities; 5 had hypoevolutism TIMP scores, and 1 with moderate aEEG abnormalities maintained a normal TIMP score, exhibiting lesser CrSO2 reduction and improved FTOE. Conclusion CrSO2 and aEEG monitoring show potential as routine assessments for neurological outcomes during neonatal ECMO. In our cohort, a tendency was observed where neonates with greater reductions in CrSO2 and more severe aEEG abnormalities experienced poorer neurological outcomes.